Recombinant Human Thrombopoietin Accelerates the Recovery of Platelet in Patients With Lower-Risk Myelodysplastic Syndrome: A Proof-of-Concept Study - Yang, Yuan; Tang, Zengwei; Ji, Jiang; Yang, Chen; Chen, Miao; Han, Bing (Frontiers in Oncology, 2021)
Aim: The effect of recombinant human thrombopoietin (rhTPO) is largely unknown in lower-risk myelodysplastic syndrome (LR-MDS). This study aimed at investigating the safety and efficacy of rhTPO in patients with LR-MDS. Methods: LR-MDS patients receiving stanozolol 2mgtid and supportive care alone (non-rhTPO) or additional rhTPO were enrolled in this study prospectively. rhTPO was given at 15000U qd for 7days/months for at least three months. Patients stopped rhTPO if platelet count was higher than 50×109/L, or had no effects after 3-month treatment. The overall response (OR), complete response (CR), platelet response, side effects, clone evolution and clinical outcome were evaluated. Result: 35 patients were enrolled, including 20 (57.1%) patients in rhTPO and 15 (42.9%) patients in non-rhTPO group. The demographic and baseline characteristic were balanced between the two groups. The platelet response was higher at 1 month and 2 months, as compared with that in non-rhTPO group (p=0.006 and p=0.001, respectively). Meanwhile, rhTPO group had a shorter time to achieve platelet transfusion free compared with non-rhTPO group (p=0.034).The hematologic response was higher at 1/2-months, as compared with that in non-rhTPO group (p=0.006 and p=0.001, respectively). No significant difference in overall response, or complete response at 1/2/3/6/12months between the two groups. One patient in rhTPO group evolved into higher risk MDS at 9 months. No significant difference in disease progression, infection, gastrointestinal disorders or drug-related liver/renal injuries were found between the two groups (p>0.05). Conclusion: Adding short-term rhTPO can accelerate the early platelet response and decrease platelet transfusion with no obvious side effects.